The impact of credit rating announcements on the bonds yield spreads of companies: A review of Turkish companies - Coşkun, Hakan (İstanbul Bilgi Üniversitesi, 2018)
[Abstract Not Available]
Kredi derecelendirme ananoslarının şirketlerin tahvil getiri Spread'lerin üzerindeki etkisi: Türk şirketleri hakkında yapılan inceleme